IT VALUE ESTIMATION USING PARTIAL ADJUSTMENT VALUATION WITH TOBIN’S Q DYNAMIC FACTOR - Doloksaribu, Lastri M. A; Abdurrahman, Lukman; Fauzi, Rokhman (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
The rapid development of Information Technology (IT) directly and indirectly forces companies to adopt IT in the company's work processes/systems. These developments and being followed by the Covid 19 pandemic directly demanded almost all lines of life, especially in companies, to utilize IT to support the continuity of processes/performance systems in the company. IT is a system used by companies to optimize company performance. To find out, it is necessary to measure IT performance in work units that adopt IT, which is called IT Value. The value of IT is a quantitative measure of the use of IT in the company whether it provides positive or negative optimization for the company. The value of IT can be used as a measure of a company's value in the market after and before using IT. Measurement of IT Value can be done in various ways, in this journal research the estimation of IT Value uses Partial Adjustment assessment with two-factor model (primary data K, L, Tobin's Q) and three-factor model (with primary data K, L, I, Q Tobin). The estimation results of the two-factor model and the three-factor model will be compared to calculate the Performance Measure of IT Value in terms of Performance Ratio (PR) in ratio units and Performance Value (PV) in rupiah. The results of the value of IT PV and PR can be used by companies as evaluation and decision-making materials for optimizing the use of IT in the company for the present and the future.